Apoptosis of tumor-infiltrating T lymphocytes: a new immune checkpoint mechanism - Zhu, J; Petit, P; Van Den Eynde, B (Springer Berlin Heidelberg, 2018)
Immunotherapy based on checkpoint inhibitors is providing substantial clinical benefit, but only to a minority of cancer patients. The current priority is to understand why the majority of patients fail to respond. Besides T-cell dysfunction, T-cell apoptosis was reported in several recent studies as a relevant mechanism of tumoral immune resistance. Several death receptors (Fas, DR3, DR4, DR5, TNFR1) can trigger apoptosis when activated by their respective ligands. In this review, we discuss the immunomodulatory role of the main death receptors and how these are shaping the tumor microenvironment, with a focus on Fas and its ligand. Fas-mediated apoptosis of T cells has long been known as a mechanism allowing the contraction of T-cell responses to prevent immunopathology, a phenomenon known as activation-induced cell death, which is triggered by induction of Fas ligand (FasL) expression on T cells themselves and qualifies as an immune checkpoint mechanism. Recent evidence indicates that other cells in the tumor microenvironment can express FasL and trigger apoptosis of tumor-infiltrating lymphocytes (TIL), including endothelial cells and myeloid-derived suppressor cells. The resulting disappearance of TIL prevents anti-tumor immunity and may in fact contribute to the absence of TIL that is typical of “cold” tumors that fail to respond to immunotherapy. Interfering with the Fas–FasL pathway in the tumor microenvironment has the potential to increase the efficacy of cancer immunotherapy.